Can the use of iron phthalocyanine-derivative mouthrinses in COVID-19 patients provide systemic benefits? Research into this potential should be considered - da Fonseca Orcina, Bernardo; Bertin, Laura; Izu Nakamura Pietro, Emilene Cristine; Pescinelli Garcia Kuroda, Juliana; Marques da Costa Alves, Lucas; Vieira Vilhena, Fabiano; da Silva Santos, Paulo Sérgio (German Medical Science GMS Publishing House, 2024)
Aim: The purpose of this brief report is to discuss the impact of an oral rinse and spray containing an iron phthalocyanine derivative as an additional therapy in hospitalized COVID-19 patients.Methods: In the first study by this group of authors published on this topic, the clinical status of 22 patients with COVID-19 who were hospitalized and receiving PDMS (phthalocyanine derivative mouth spray) was assessed using the Karnofsky scale (KS) for thtree days (D0, D2, and D4). In another study, the laboratory data (CBC, D-dimer, Ferritin, and C-reactive protein [CRP]) of 41 patients hospitalized with COVID-19 who took part in a randomized clinical trial with an MIPD (mouthwash with iron phthalocyanine derivative) were evaluated retrospectively on the first day of intervention (D1) and 48 hours later (D2). The present study used these data to determine a correlation between clinical symptoms and laboratory data.Results: In individuals receiving PDMS and evaluated using the KS, a statistically significant intra-group difference (p=0.03, Friedman's test) was identified. The Durbin-Conover test found a significant difference between D0 and D2 (p=0.008). Laboratory data from only 9 patienn the experimental group and 13 patients in the control group were found in the retrospective analysis. There were no statistically significaonfounders in the survival analysis using the Cox regression model. In the descriptive analysis, the intervention group's CRP was lower than thf the control group.Conclusion: PDMS demonstrated considerable clinical improvement in patients, whereas MIPD appears to lower CRP, an inflammatory marker, in descriptive analysis.